1984
DOI: 10.1002/1097-0142(1984)54:4<785::aid-cncr2820540434>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A cancer register-based case study of occupations of patients with acute myeloid leukemia

Abstract: All 636 cases of acute myeloid leukemia (AML) reported to the Finnish Cancer Registry between 1971 and 1977 inclusive were compared with patients with other forms of cancer (non‐AML) from the same registry. We found no increasing trend in the incidence of AML for either sex, but we found some evidence for regional clusters in certain provinces of Finland. A statistically significant higher incidence was found for men than women in the age group of 50 to 80 years. Classification according to occupation at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Seventeen cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 16 case-control studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were identified as fulfilling the inclusion criteria.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 99%
“…Seventeen cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 16 case-control studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were identified as fulfilling the inclusion criteria.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 99%
“…In addition, exposure to other organic solvents (13), ex-tremely low frequency electromagnetic fields (ELMF) (14)(15)(16)(17)(18), hair dyes (19)(20)(21), pesticides (22), petroleum products and exhaust gases (23), animalborne viruses (24), and forestry work (25) have been indicated as risk factors, albeit with conflicting results (12,26).…”
mentioning
confidence: 99%
“…In general, no industries or occupations entailing exposure to DE were listed in these reports (eg, a study of over 200,000 cancer cases included during 1979 -1984 in the cancer registry from New Jersey 34 ; a study of 636 AML cases included during 1971-1977 in the Finnish Cancer Registry 35 ; a study based on linkage between occupational records of Swedish women at the 1960 census and 1961-1979 Cancer Registry data 36 ; a study of 252 AML cases and 1161 hospital-based controls from Italy 37 ; a study of 260 female leukemia cases and 828 population controls from Italy 38 ; and a study of a sample of 18,733 U.S. death certificates from 1986 39 ). …”
Section: Additional Studiesmentioning
confidence: 97%